Bioactivity of Common Pesticidal Plants on Fall Armyworm Larvae (Spodoptera frugiperda) - Phambala, Kelita (Plants (Basel), 2020)
The fall armyworm (FAW), Spodoptera frugiperda (Lepidoptera: Noctuidae) is a recent invasive pest species that has successfully established across sub-Saharan Africa where it continues to disrupt agriculture, particularly smallholder cereal production. Management of FAW in its native range in the Americas has led to the development of resistance to many commercial pesticides before its arrival in Africa. Pesticide use may therefore be ineffective for FAW control in Africa, so new and more sustainable approaches to pest management are required that can help reduce the impact of this exotic pest. Pesticidal plants provide an effective and established approach to pest management in African smallholder farming and recent research has shown that their use can be cost-beneficial and sustainable. In order to optimize the use of botanical extracts for FAW control, we initially screened ten commonly used plant species. In laboratory trials, contact toxicity and feeding bioassays showed differential effects. Some plant species had little to no effect when compared to untreated controls; thus, only the five most promising plant species were selected for more detailed study. In contact toxicity tests, the highest larval mortality was obtained from Nicotiana tabacum (66%) and Lippia javanica (66%). Similarly, in a feeding bioassay L. javanica (62%) and N. tabacum (60%) exhibited high larval mortality at the highest concentration evaluated (10% w/v). Feeding deterrence was evaluated using glass-fibre discs treated with plant extracts, which showed that Cymbopogon citratus (36%) and Azadirachta indica (20%) were the most potent feeding deterrents among the pesticidal plants evaluated. In a screenhouse experiment where living maize plants infested with fall armyworm larvae were treated with plant extracts, N. tabacum and L. javanica were the most potent species at reducing foliar damage compared to the untreated control whilst the synthetic pesticide chlorpyrifos was the most effective in reducing fall armyworm foliar damage. Further field trial evaluation is recommended, particularly involving smallholder maize fields to assess effectiveness across a range of contexts.